Development of the ReaxFF(CBN) reactive force field for the improved design of liquid CBN hydrogen storage materials - Pai, Sung Jin; Yeo, Byung Chul; Han, Sang Soo (ROYAL SOC CHEMISTRY, 2016)
Liquid CBN (carbon-boron-nitrogen) hydrogen-storage materials such as 3-methyl-1,2-BN-cyclopentane have the advantage of being easily accessible for use in current liquid-fuel infrastructure. To develop practical liquid CBN hydrogen-storage materials, it is of great importance to understand the reaction pathways of hydrogenation/dehydrogenation in the liquid phase, which are difficult to discover by experimental methods. Herein, we developed a reactive force field (ReaxFF(CBN)) from quantum mechanical (QM) calculations based on density functional theory for the storage of hydrogen in BN-substituted cyclic hydrocarbon materials. The developed ReaxFFCBN provides similar dehydrogenation pathways and energetics to those predicted by QM calculations. Moreover, molecular dynamics (MD) simulations with the developed ReaxFF(CBN) can predict the stability and dehydrogenation behavior of various liquid CBN hydrogen-storage materials. Our simulations reveal that a unimolecular dehydrogenation mechanism is preferred in liquid CBN hydrogen-storage materials. However, as the temperature in the simulation increases, the contribution of a bimolecular dehydrogenation mechanism also increases. Moreover, our ReaxFF MD simulations show that in terms of thermal stability and dehydrogenation kinetics, liquid CBN materials with a hexagonal structure are more suitable materials than those with a pentagonal structure. We expect that the developed ReaxFF(CBN) could be a useful protocol in developing novel liquid CBN hydrogen-storage materials.
Keywords: DYNAMICS; SYSTEMS; CYCLOHEXANE; SIMULATIONS; NANOTUBES; DENSITY